The factors affecting solvency and credit risks in MENA banks - Lamya M. Gadou (Journal of Corporate Finance Management and Banking System, 2025)
This study examines the impact of bank-specific and macroeconomic variables on bank risk measures proxied by solvency risk (Z-score) and credit risk (NPLs). Fixed and random effects panel regression models are adopted the generalized method of moments (GMM) dynamic technique for 138 banks in 12 MENA countries (2005-2022). Which is further sub-divided into two groups, namely GCC and MPC for comparative analysis to reveal differences in terms of importance of risk determinants. The results indicate mainly that leverage raises both solvency and credit risks. An increase in income diversability reduces solvency risk and a larger bank size mitigates credit risk. Moreover, economic growth significantly reduces solvency risk but inflation erodes bank financial stability. Regarding the GCC, there is a positive relationship between size and solvency risk. Also, economic growth enhances credit quality while liquidity worsens this portfolio. Considering the MPC sample, leverage is the most important factor raising credit risk. Profitability has a positive effect on Z-score, thereby lowers solvency risk. These findings suggest that banks in the MENA region can enhance their stability by focusing on improving profitability and operational efficiency while managing leverage levels. Policymakers may also consider fostering economic growth to support banking sector stability.